2018
DOI: 10.1038/s41598-018-34701-3
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt1 has an essential function despite the absence of CpG DNA methylation in the red flour beetle Tribolium castaneum

Abstract: Epigenetic mechanisms, such as CpG DNA methylation enable phenotypic plasticity and rapid adaptation to changing environments. CpG DNA methylation is established by DNA methyltransferases (DNMTs), which are well conserved across vertebrates and invertebrates. There are insects with functional DNA methylation despite lacking a complete set of Dnmts. But at least one of the enzymes, DNMT1, appears to be required to maintain an active DNA methylation system. The red flour beetle, Tribolium castaneum, lacks Dnmt3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 64 publications
6
70
0
1
Order By: Relevance
“…ovaries. Further, maternal silencing of this gene caused a developmental arrest in offspring embryos (Schulz et al, 2018). Taking together these studies and our findings, we postulate an evolutionarily conserved role of the DNMT1-DMAP1 complex beyond embryonic development including a role in ovary maturation and female fecundity.…”
Section: Discussionsupporting
confidence: 73%
“…ovaries. Further, maternal silencing of this gene caused a developmental arrest in offspring embryos (Schulz et al, 2018). Taking together these studies and our findings, we postulate an evolutionarily conserved role of the DNMT1-DMAP1 complex beyond embryonic development including a role in ovary maturation and female fecundity.…”
Section: Discussionsupporting
confidence: 73%
“…While Dnmt1 is expressed at all life stages, it is upregulated in ovaries, suggesting a role in reproduction. Finally, parental RNAi of Dnmt1 demonstrated that T. castaneum requires maternal expression of Dnmt1 for early embryogenesis (Schulz et al, 2018). Together, these studies suggest a germ cell specific function for Dnmt1 in insects.…”
Section: Introductionmentioning
confidence: 80%
“…Expression of Dnmt1 is high in eggs and embryos relative to other tissues in several insect species (Yan et al, 2015;Schulz et al, 2018, this study). Knocking down Dnmt1 expression in eggs and embryos results in embryo lethality (Zwier et al, 2012;Schulz et al, 2018;Bewick et al, 2019). Third, there is a suggestion that DNA methylation may be important in stability of germ cells (Takashima et al, 2009;Bewick et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations